Comparison of barbed suture and conventional suture in laparoendoscopic single-site myomectomy - Xie, Weimin; Tang, Shuiping; Wang, Zhangyi; Liu, Xiaohang; Wang, Li; Tang, Rong; Tang, Chaoqun; Xie, Chunyan (Frontiers in Oncology, 2025)
ObjectiveTo compare surgical outcomes of laparoendoscopic single-site myomectomy (LESS-M) for uterine myomas using barbed suture versus conventional suture.MethodsData were collected from all women with uterine myomas who underwent LESS-M at three institutions. Patients were managed by LESS-M with either barbed suture or conventional suture.ResultsOperative time was significantly lower in the barbed suture group in comparison with the conventional suture group (65.4 ± 10.7 min vs. 78.02 ± 14.2 min, P = 0.000). Similarly, the amount of blood loss was lower in the barbed suture group than in the conventional suture group (158.1 ± 85.2 mL versus 209.6 ± 85.9, P = 0.000). Accordingly, the change in hemoglobin levels in the barbed suture group was lower than in the conventional suture group (16.6 ± 5.9 g/L versus 21.0 ± 4.8, P = 0.000). Conversely, there were no statistically significant differences for blood transfusion, the postoperative pain VAS score assessed at 24 hours, length of hospital stay, conversion, and perioperative complication rates between the two groups (P > 0.05 for all).ConclusionThe use of barbed suture may reduce operative time, blood loss, and hemoglobin change during LESS-M, which may be an optimal and efficient alternative to conventional suture.